Self-Assembly of Plasmonic Nanoantenna-Waveguide Structures for Subdiffractional Chiral Sensing - Rothe, Martin; Zhao, Yuhang; Mueller, Johannes; Kewes, Guenter; Koch, Christoph T.; Lu, Yan; Benson, Oliver (ACS nano, 2021)
Spin-momentum locking is a peculiar effect in the near-field of guided optical or plasmonic modes. It can be utilized to map the spinning or handedness of electromagnetic fields onto the propagation direction. This motivates a method to probe the circular dichroism of an illuminated chiral object. In this work, we demonstrate local, subdiffraction limited chiral coupling of light and propagating surface plasmon polaritons in a self-assembled system of a gold nanoantenna and a silver nanowire. A thin silica shell around the nanowire provides precise distance control and also serves as a host for fluorescent molecules, which indicate the direction of plasmon propagation. We characterize our nanoantenna-nanowire systems comprehensively through correlated electron microscopy, energy-dispersive X-ray spectroscopy, dark-field, and fluorescence imaging. Three-dimensional numerical simulations support the experimental findings. Besides our measurement of far-field polarization, we estimate sensing capabilities and derive not only a sensitivity of 1 mdeg for the ellipticity of the light field, but also find 103 deg cm2/dmol for the circular dichroism of an analyte locally introduced in the hot spot of the antenna-wire system. Thorough modeling of a prototypical design predicts on-chip sensing of chiral analytes. This introduces our system as an ultracompact sensor for chiral response far below the diffraction limit.
CRIS-Team Scopus Importer:2023-04-20
Keywords: chirality; circular dichroism; core-shell; nano-optics; nanoparticle assemblies; plasmonics; spin-orbit coupling